Question and Answers Forum

All Questions      Topic List

Set Theory Questions

Previous in All Question      Next in All Question      

Previous in Set Theory      Next in Set Theory      

Question Number 35703 by scientist last updated on 22/May/18

Answered by arcana last updated on 17/Oct/18

tomando la propiedad de funcion de medida n  A,B conjuntos finitos  n(A∪B)=n(A)+n(B)−n(A∩B)  asi  • n((A∪B)∪(C∪D))=n(A∪B)+n(C∪D)−n((A∪B)∩(C∪D))  =[n(A)+n(B)−n(A∩B)]+[n(C)+n(D)−n(C∩D)]−n(((A∪B)∩C)∪((A∪B)∩D))  (/)(/)(/)(/)(/)(/)(/)(/)(/)(/)(/)(/)(/)(/)(/)(/)(/)(/)(/)(/)(/)  ahora hallamos n([(A∪B)∩C]∪[(A∪B)∩D])  n([(A∪B)∩C]∪[(A∪B)∩D])=n((A∪B)∩C)+  n((A∪B)∩D)−n((A∪B)∩(C∩D))    =[n(A∩C)+n(B∩C)−n(A∩B∩C)]+  [n(A∩D)+n(B∩D)−n(A∩B∩D)]−  [n(A∩C∩D)+n(B∩C∩D)−n(A∩B∩C∩D)]  (/)(/)(/)(/)(/)(/)(/)(/)(/)(/)(/)(/)(/)(/)(/)(/)(/)(/)(/)(/)(/)  por lo anterior podemos reescribir • como  • n((A∪B)∪(C∪D))=n(A)+n(B)+n(C)+n(D)−n(A∩B)−n(C∩D)−  n(A∩C)−n(B∩C)+n(A∩B∩C)]−  n(A∩D)−n(B∩D)+n(A∩B∩D)]+  n(A∩C∩D)+n(B∩C∩D)−n(A∩B∩C∩D)

tomandolapropiedaddefunciondemedidanA,Bconjuntosfinitosn(AB)=n(A)+n(B)n(AB)asin((AB)(CD))=n(AB)+n(CD)n((AB)(CD))=[n(A)+n(B)n(AB)]+[n(C)+n(D)n(CD)]n(((AB)C)((AB)D))ahorahallamosn([(AB)C][(AB)D])n([(AB)C][(AB)D])=n((AB)C)+n((AB)D)n((AB)(CD))=[n(AC)+n(BC)n(ABC)]+[n(AD)+n(BD)n(ABD)][n(ACD)+n(BCD)n(ABCD)]porloanteriorpodemosreescribircomon((AB)(CD))=n(A)+n(B)+n(C)+n(D)n(AB)n(CD)n(AC)n(BC)+n(ABC)]n(AD)n(BD)+n(ABD)]+n(ACD)+n(BCD)n(ABCD)

Terms of Service

Privacy Policy

Contact: info@tinkutara.com